Merdeka Belajar di Era Digital - Hendrik Legi; Hotmian Lumban Toruan (PT. ALHAFI BERKAH INDONESIA, 2024)
Merdeka Belajar in the digital era offers a new paradigm in education, allowing individuals to learn according to their needs and interests without being bound by physical boundaries or a rigid curriculum. The use of technology, such as online learning and games, allows wider access to information and learning. However, the digital divide between urban and rural areas and paradigm changes in the world of education are the main challenges. Efforts are needed to increase access to technology throughout Indonesia and change mindsets in education. Changing learning paradigms requires teachers to become learning facilitators who are able to accommodate students' individual differences. By overcoming these challenges, Merdeka Belajar in the digital era can improve the quality of education, develop student creativity and innovation, strengthen collaboration between students and teachers, and increase educational accessibility. The concept of Independent Learning is expected to create an educational environment that is inclusive, adaptive and relevant to the demands of the times.